Pemanfaatan Aplikasi Platform Merdeka Mengajar (PMM) sebagai Sarana Supervisi Akademik dalam Meningkatkan Kinerja Guru - Lastini, Fitri; Narimo, Sabar; Fuadi, Djalal; Minsih, Minsih (Jayapangus Press, 2025)
The background of this study is the importance of effective academic supervision in improving teacher performance, especially in the digital era, which demands efficiency and effectiveness in the monitoring and professional development processes. The Merdeka Mengajar Platform (PMM) application is expected to be a solution in facilitating more measurable and efficient academic supervision, as well as providing faster feedback to teachers. This study aims to explore the use of PMM as an academic supervision tool by school principals to improve teacher performance at SDN 02 Jatiwarno. The research method used is qualitative, with data collection techniques through interviews, observations, and document analysis. The subjects of this study are the principal and teachers involved in the academic supervision program using PMM. The results of the study show that the use of PMM has a positive impact on teacher performance. The principal can monitor the development of teachers in real-time, provide faster feedback, and identify areas that require more attention. Additionally, teachers feel supported in their professional development through the training features provided within the application. However, there are challenges in terms of technology adaptation, particularly for teachers who are not familiar with using digital applications. In conclusion, PMM can improve the efficiency of academic supervision and teacher performance, but further training is needed to maximize the use of this application. This study recommends that continuous training be provided to enhance competence in using PMM for academic supervision.